Evaluasi Kenyamanan Termal Masjid Baitul Musyahadah Kota Banda Aceh - Fuady, Mirza; Kevin, Andrian; Ridwan, Nasrullah; Buraida, Buraida; Munadi, Rizal (Universitas Syiah Kuala, 2024)
Many mosques in the city of Banda Aceh have used artificial ventilation systems to achieve thermal comfort conditions in the interior of the mosque. Meanwhile, the Baitul Musyahadah Mosque, which is classified as a large mosque in Banda Aceh City, currently still maintains an open mosque building design and utilizes a natural ventilation system. In this community service activity, field research was carried out with the aim of evaluating thermal comfort in the interior of the Baitul Musyahadah Mosque. The research method uses a quantitative descriptive approach by collecting data through field observations and measurements, according to variables that influence thermal comfort including air temperature, air humidity and wind speed. The results obtained regarding the thermal comfort conditions of the space in the Baitul Musyahadah Mosque are (a) the average value of the effective temperature in the building falls within the limits of a warm comfortable sensation; (b) the average value of air humidity in the building is within comfortable limits; (c) the wind speed value in the room is very weak. Furthermore, based on the results of the analysis and simulation of thermal comfort in the mosque, improvements to the opening aspects which influence increasing wind speed in the mosque are recommended to support passive thermal comfort.